2017
DOI: 10.1108/nfs-09-2016-0136
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between skin color, sun exposure, UV protection, fish intake and serum levels of vitamin D in Japanese older adults

Abstract: Purpose This paper aims to observe the possible relationship between skin color, sun exposure level, UV protection and food intake and serum levels of 25(OH) D in Japanese older adults. Design/methodology/approach Elderly (n = 131; 65-93 years old), followed by the Tokyo Metropolitan Institute of Gerontology in the Kusatsu (36°N) received a self-applicable questionnaire about the quantity and quality of the daily sun exposure and behavior to avoid the sun. A color analyzer measured each red (R), green (G) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Because serum 25(OH)D concentration, triglycerides, glucose, glycohemoglobin, insulin, C-peptide, C-reactive protein, Homeostatic Model Assessment-Insulin Resistance, and homocysteine were skewed, to satisfy the normality, natural logarithm transformed values were used. 3 Homeostatic Model Assessment-Insulin Resistance: Fasting insulin (µU/mL) × fasting glucose (mg/dL)/405.…”
Section: Sample Derivation and Eligibility Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Because serum 25(OH)D concentration, triglycerides, glucose, glycohemoglobin, insulin, C-peptide, C-reactive protein, Homeostatic Model Assessment-Insulin Resistance, and homocysteine were skewed, to satisfy the normality, natural logarithm transformed values were used. 3 Homeostatic Model Assessment-Insulin Resistance: Fasting insulin (µU/mL) × fasting glucose (mg/dL)/405.…”
Section: Sample Derivation and Eligibility Criteriamentioning
confidence: 99%
“…The association between serum 25(OH)D concentrations and prevalence of MetS is presented in 3 Significance for the effect of serum 25(OH)D in the multivariable adjusted regression. 4 Data were adjusted for age, gender, race-ethnicity, physical activity, consumption of supplements, smoking status, and alcohol consumption, as well as for interactions between serum 25(OH)D and gender; serum 25(OH)D and race-ethnicity; race-ethnicity and gender; gender and alcohol consumption; and physical activity and alcohol consumption.…”
Section: Serum 25(oh)d Concentrations Mets and Diabetesmentioning
confidence: 99%
“…Vitamin D is a lipophilic nutrient that was obtained from the diet and vitamin D supplements. Although vitamin D is synthesized endogenously in the skin when exposed to Sun's UV-B light, the amount of vitamin D that is synthesized in this process is highly variable and affected by several factors, such as latitude, time of the day, skin tone, amount of clothing worn, and use of sunblock lotions [1][2][3]. Interest in vitamin D has grown in recent times because hypovitaminosis D has been found to be related to non-calcemic ailments, such as metabolic syndrome [4,5] obesity [6], diabetes mellitus [7], cancer [8,9], cardiovascular diseases [10], and depression [11].…”
Section: Introductionmentioning
confidence: 99%
“…Some risk factors relative to VD deficiency have been recognized, such as dietary habits and sun exposure [ 14 , 15 ]. Previous studies found that the Japanese elderly population with sufficient levels of 25(OH)D presented with a higher fish intake value (12 times per week) [ 16 ]. A cohort study indicated that the main dietary sources of VD among elderly Germans were fish, eggs, oils, bakery products, and milk or dairy products [ 17 ].…”
Section: Introductionmentioning
confidence: 99%